The Influence Of Product Perceived Quality, Service, Environment And Assortment On Customer Loyalty With Customer Satisfaction As An Intervening Variable In Angkringan UMKM In Mojokerto Regency - Setia Pratama, Ade; Sudarmiatin, Sudarmiatin; Wishnu Wardhana, Ludi (International Journal of Science, Technology & Management, 2023)
The development of the culinary business in Indonesia began to bloom in the 1970s with the rapid emergence of many restaurants which became an opportunity for companies to develop their business. One of these developments is the emergence of the trend of roadside angkringan which is now reaching millennial generation consumers and has become a new favorite sector that is worth developing. The presence of this angkringan answers the desires and needs of the lower middle class community and has big implications in driving the community economy.This research aims to find out the influence of Product Perceived Quality, Service, Environment, Assortment on Loyalty through Satisfaction. The expected benefit of this research is to increase the body of knowledge in the field of management, especially how big the influence of satisfaction is so that it increases loyalty which will ultimately increase purchases. The research method used is a quantitative method with data processing using AMOS. Data collection was carried out by distributing questionnaires to 130 respondents with the characteristics of male and female respondents aged 18-60 years, who visited several food courts spread across the Mojokerto Regency area at least twice a year. The research results show that Product Perceived Quality with a regression coefficient of 0.426 positively and significantly influences satisfaction; Service with a regression coefficient of 0.242 positively and significantly influences Satisfaction, Environment with a regression coefficient of 0.136 positively and significantly influences Satisfaction. Assortment, with a regression coefficient of 0.748, positively and significantly influences Satisfaction, and Satisfaction with a regression coefficient of 0.633 positively and significantly influences loyalty